2000
DOI: 10.1523/jneurosci.20-19-07307.2000
|View full text |Cite
|
Sign up to set email alerts
|

GluR3 Autoantibodies Destroy Neural Cells in a Complement-Dependent Manner Modulated by Complement Regulatory Proteins

Abstract: GluR3 autoantibodies have been implicated in the development of Rasmussen's encephalitis, a rare neurodegenerative disease of humans characterized by epilepsy and degeneration of a single cerebral hemisphere. GluR3 autoantibodies are found in some Rasmussen's encephalitis patients, and GluR3 antibodies raised in rabbits destroy cultured cortical cells in a complementdependent manner. In this study, the cellular targets of antiGluR3 antisera-mediated cytotoxicity were examined in mixed primary neuronal-glial cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 44 publications
3
61
0
3
Order By: Relevance
“…Mechanisms similar to those by which MAC deposition evokes seizures likely underlie the cytotoxic consequences of MACs in the present study. Although the deposition of one or a few MACs might evoke cation flux and depolarization, triggering high-frequency firing, the diffusion of ions down their electrochemical gradients through large numbers of MACs would be expected to induce cell swelling and osmotic lysis, the hallmarks of death of cortical neurons undergoing lethal attack by complement in vitro (Whitney and McNamara, 2000). Importantly, analyses of diverse nucleated cell types have elucidated an elaborate set of defense mechanisms aimed at fending off MAC deposition on cell membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms similar to those by which MAC deposition evokes seizures likely underlie the cytotoxic consequences of MACs in the present study. Although the deposition of one or a few MACs might evoke cation flux and depolarization, triggering high-frequency firing, the diffusion of ions down their electrochemical gradients through large numbers of MACs would be expected to induce cell swelling and osmotic lysis, the hallmarks of death of cortical neurons undergoing lethal attack by complement in vitro (Whitney and McNamara, 2000). Importantly, analyses of diverse nucleated cell types have elucidated an elaborate set of defense mechanisms aimed at fending off MAC deposition on cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of MAC formation on cortical neurons in these diverse diseases notwithstanding, whether the deposition of MAC in cortical gray matter in the mammalian brain has deleterious consequences is uncertain. The determination that the formation of MAC in muscle cell membranes results in depolarization (Jackson et al, 1981) together with the cytotoxic effects of MAC in cortical neurons in vitro (Whitney and McNamara, 2000) led us to hypothesize that MAC deposition on neurons could trigger seizures and neurodegeneration. We tested this hypothesis by sequential infusion of individual proteins of the membrane attack pathway into the rat hippocampus to form MAC in vivo.…”
mentioning
confidence: 99%
“…(1994), , Levite and Hermelin (1999), Whitney and McNamara (2000) and Koustova et al (2001) Anti-dsDNA…”
Section: Rasmussen's Encephalitismentioning
confidence: 99%
“…Specifically, anti-GluR3 Ab's were found in some patients with various types of epilepsy, suffering primarily from non-inflammatory focal epilepsy (Wiendl et al, 2001), or from severe, early-onset and intractable seizures (Mantegazza et al, 2002). Further studies and findings suggested that anti-GluR3 Ab's may indeed play a pathogenic role in epilepsy, since they can: (a) bind brain cells and structures Whitney and McNamara, 2000;Frassoni et al, 2001;Bernasconi et al, 2002), (b) activate ionotropic GluR's and evoke ion currents, acting like a "novel" glutamate agonist (Twyman et al, 1995;Koustova et al, 2001), (c) kill neurons and glia cells via excitotoxicity-a fatal overactivation of the glutamate receptors Koustova et al, 2001), alike that caused by excess glutamate in various pathological situations (Olney, 1990;Choi, 1992), and (d) activate the destructive complement system within the central nervous system (CNS), causing at first death of astrocytes, and then death of neurons (He et al, 1998;Whitney and McNamara, 2000). In this context it is of interest to mention that the serial recruitment of all the complement factors in the CNS was recently shown to induce seizures (Xiong et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cell death was assessed by measuring lactate dehydrogenase (LDH) activity in culture supernatants by a spectrophotometric method (Whitney and McNamara, 2000). Data are presented as the means Ϯ S.E.M.…”
Section: Methodsmentioning
confidence: 99%